Intramedullary screw fixation for metacarpal shaft fractures: a biomechanical human cadaver study. (July 2020) - Labèr, Raffael; Jann, David; Behm, Pascal; Ferguson, Stephen J.; Frueh, Florian S.; Calcagni, Maurizio
Intramedullary cannulated compression screws have been introduced for the fixation of unstable metacarpal fractures. In the present study, this technique was compared with dorsal compression plating to evaluate its biomechanical performance in stabilizing metacarpal shaft fractures. In a first set of experiments, the biomechanical characteristics of the screws were analysed in an artificial bone model. In subsequent experiments, midshaft osteotomies were performed in human cadaver metacarpals, followed by plating or intramedullary screw osteosynthesis. The metacarpals were tested to failure in cantilever bending, following a stepwise increasing cyclic loading protocol. We found a significantly lower load at failure and a significantly lower number of cycles to failure in the intramedullary screw group, but both methods offered sufficient stability under these loads. With reference to published loads on the metacarpals during use of the hand, we conclude that intramedullary osteosynthesis yields sufficient strength and stiffness for early active motion. A difference in its fixation stability is noted compared with plate fixation, which may not be clinically relevant.